At home in the tropics: seasonal niche-tracking by the Yellow-green Vireo, Vireo flavoviridis, an intratropical migrant - Alejandra Ochoa-Gonzále; Octavio R. Rojas-Soto; David A. Prieto-Torres; María del Coro Arizmendi; Adolfo G. Navarro-Sigüenza (Revista Mexicana de Biodiversidad)
Migratory birds move geographically by tracking specific climatic conditions through time. However, we lack information about the climatic conditions birds are tracking, especially in intratropical migrants, whose movements are contained inside the tropics. The Yellow-green Vireo Vireo flavoviridis is an intratropical migrant whose migration patterns remain only partially documented and understood. Using GBIF presence records and WorldClim monthly climatic layers, we reconstructed ecological niche for Yellow-green Vireo’ reproductive and non-reproductive seasons. Then, we used a niche overlap analysis, based on a PCA-env approach and similarity tests, to assess overlap in climatic niches between seasons. We also projected climatic niches onto their spring and fall migration to evaluate the climatic conditions tracked by the species in transitional months. Overall, models revealed significant geographic inter-prediction between seasons. Similarity analyses showed high niche overlap between seasons; however, they failed to reject the null hypothesis of niche similarity. As expected by the hypothesis of niche conservatism in the tropics, Yellow-green Vireo is a niche follower. This information will help to clarify evolution of intratropical migration and provide ecological information for future conservation plans.